Cryptocurrency and Its State of Research - Gunarso, Gatot; Stephanie (International Dialogues on Education Journal, 2022)
This article maps the existing academics and working papers about cryptocurrency, or digital currency that uses blockchain. Cryptocurrency is one of the applications of blockchain that can accelerate economic digitalization within countries, which in the end could improve economic efficiency, effectiveness, and access for citizens. By the type of issuers, cryptocurrencies can be placed into three categories: central bank-issued digital currency, private institution digital currency, and peer-to-peer crypto-assets. The advent of cryptocurrencies requires strong regulatory frameworks to protect the users, ethics guidelines to direct the development, risk benefits study to identify pitfalls, users’ psychology, law enforcement guidelines to ensure a safe environment, and economic initiatives to provide society with maximized benefits. This paper shows research findings, methods, and future research directions in cryptocurrency.